The impact of technological innovation for clean and green products on the environment - Meena, Ram Khiladi (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
This review paper examines the profound impact of technological innovations in the development and implementation of clean and green products on the environment. It provides a comprehensive analysis of various cutting-edge technologies, such as renewable energy solutions, sustainable materials, and eco-friendly manufacturing processes, and their contributions to reducing environmental footprints. The paper highlights advancements in technology that enhance resource efficiency, minimize waste, and lower greenhouse gas emissions. It also discusses the challenges and opportunities associated with integrating these technologies into existing systems, and their potential to drive significant environmental improvements. By synthesizing current research and case studies, this review aims to offer valuable insights into how technological innovation can foster a cleaner, greener, and more sustainable future.